Daya Antibakteri Ekstrak Daun Beluntas (Pluchea Indica Less) Terhadap Streptococcus Viridans (In Vitro) - Agni Febrina Pargaputri; M. Mudjiono; Agus Subiwahjudi (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Pluchea indica Less leaves is a species of plants that has several chemical properties. It consists of flavonoids, tanine, and essensial oil which had been reported as antibacterial agents. Streptococcus viridans is the most common bacteria found in infected root canal teeth, and the extract of Pluchea indica Less leaves could be potentially used as one of root canal sterilization dressing in root canal teeth. Purpose: The aim of this study was to determine antibacterial activity and Minimum Bactericidal Concentration (MBC) of Pluchea indica Less leaves extract against Streptococcus viridans. Materials and Methods: The antibacterial testing of Pluchea indica Less leaves extract was performed using dilution method against Streptococcus viridans. The tube with concentration extract of 25% was showed no visible turbidity, while the tube with concentration extract of 12,5% was showedgrowth of Streptococcus viridans. We made range between concentration 12,5% until 25% to determine the Minimum Bactericidal Concentration (MBC) of Pluchea indica Less leaves extract. The result of antibacterial activity of Pluchea indica Less leaves extract was determined by measure the growth of Streptococcus viridans using colony count. Result: The result showed that Pluchea indica Less leaves extract was able to inhibit the growth of Streptococcus viridans on concentration 12,5%-25%. The results of Anova statistical test (significant value <0,05) showed significant different among each concentration of Pluchea indica Less leaves extract. Conclusion: Pluchea indica Less leaves extract had antibacterial activity against Streptococcus viridans. Minimum Bactericidal Concentration of Pluchea indica Less leaves extract was performed in concentration 12,5%-25%, which was could kill more than 99% growth of Streptococcus viridans.